The use of psychotropic medication for people with intellectual disabilities and behaviours that challenge in the context of a community multidisciplinary team approach. (4th October 2017) - Niven, Abigail; Goodey, Rebecca; Webb, Alison; Shankar, Rohit
Abstract : Accessible Summary: Lots of people with intellectual disabilities in the UK are given medication to manage their behaviours and the NHS wants this to stop. In Cornwall, we wanted to see how often we give medication to people instead of other health care such as communication or occupational assessments etc. We found that around half the people we work with because of their behaviours get medication to manage their feelings and many do not get other assessments. We want to change this in Cornwall and stop over medicating people by learning from this study. Abstract: Background: The use of psychotropic medication to manage challenging behaviours of people with intellectual disabilities is a contentious issue which NHS England has now focused on. This paper looks to evaluate this within the multidisciplinary context. Method: Records of clients ( n = 106) open to a Community Intellectual Disabilities team for care relating to challenging behaviours were examined. Those recommended psychotropic medications in the absence of a mental health diagnosis were scrutinised for supporting MDT assessments. Results: Over half the clients with challenging behaviours were being prescribed psychotropic medications and many of those had very few MDT assessments to inform care. Conclusions: This study demonstrates the extent psychotropics are used in the absence of MDT informed support for people with intellectual disabilities and behaviours that challenge. A vision to simply withdraw such medication might be simplistic. Local MDT plans are in development to systematically reduce reliance on this type of restrictive practice.